The reasons of decreasing trend of female labour force participation in Turkey: The role of conservatism - Idil Göksel (Izmir University of Economics, Department of Economics, 2012)
The aim of this paper is to investigate the main determinants of the participation decision of females in the labour force in Turkey. Turkey is a particularly important case as, unlike in many other countries, female labour force participation has shown a decreasing trend in the last 50 years. This paper aims to elaborate on the causes of this decrease. In addition to the main determinants found in previous literature, this paper adds a new variable that influences female labour force participation in Turkey: Conservatism and the role of traditional and social norms. An original proxy for conservatism is created by using a unique data set about perceptions. Four indices that might influence conservatism are formed: Tradition, social norms, men's decision power, and conservatism. The results are in accordance with the previous literature in emphasizing that urbanization, and education level play an important role in the participation decision of women. However, these factors are not sufficient to explain the decline in female labour force participation. This paper presents a new concept by showing that social norms, tradition and men's higher bargaining power play a negative role in the probability of women working in urban areas, while they do not have any significant influence in rural areas. Furthermore, this paper shows a new possible explanation for the link between urbanization and female labour force participation. Higher urbanization causes higher conservatism, which leads to lower female labour force participation.
Keywords: J16; J21; 330; female labour force participation; gender; conservatism; Erwerbstätigkeit; Weibliche Arbeitskräfte; Soziale Norm; Konservatismus; Türkei